2005
DOI: 10.1158/0008-5472.can-04-4244
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-3 Promotes the Growth of Hepatocellular Carcinoma by Stimulating Canonical Wnt Signaling

Abstract: Glypican-3 (GPC3) is a heparan sulfate proteoglycan that is bound to the cell membrane by a glycosyl-phosphatidylinositol anchor. GPC3 is expressed by most hepatocellular carcinomas but not by normal hepatocytes and benign liver lesions. We report here that GPC3 stimulates the in vitro and in vivo growth of hepatocellular carcinoma cells by increasing autocrine/paracrine canonical Wnt signaling. Coimmunoprecipitation experiments showed that GPC3 is able to form complexes with Wnts, and cell-binding assays indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
439
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(458 citation statements)
references
References 73 publications
16
439
2
1
Order By: Relevance
“…GPC3 regulates availability of Wnt proteins. 12 We also show in this study that there is an apparent increase in gene dosage for GPC3, suggesting that this gene is amplified in some HCC (Fig. 3).…”
Section: Biologic Significance Of Differentially Expressed Genes Betwsupporting
confidence: 68%
“…GPC3 regulates availability of Wnt proteins. 12 We also show in this study that there is an apparent increase in gene dosage for GPC3, suggesting that this gene is amplified in some HCC (Fig. 3).…”
Section: Biologic Significance Of Differentially Expressed Genes Betwsupporting
confidence: 68%
“…Interestingly, Wnt ligands are lipid-modified (34,41,42), and a lipid raft localization has been reported for Wnt1 (34). Additionally, glypicans, which are established HSPG partners for Wnt signaling (43,44), also localize to lipid rafts (45,46), as does the Wnt co-receptor LRP6 (47). Therefore, for optimal signaling it would seem most favorable if the Sulfs are concentrated in the same membrane microdomain as these other elements of Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Glypicans play an important role in developmental morphogenesis and are known to be modulators for the Wnt signaling pathway (14)(15)(16)(17). It has been shown that GPC3, another member of the glypican family, may function as a coreceptor for Wnt and facilitate the Wnt/Frizzled binding in hepatocellular carcinoma cells (18,19).…”
mentioning
confidence: 99%